2018
DOI: 10.25182/jgp.2018.13.1.33-38
|View full text |Cite
|
Sign up to set email alerts
|

Hydration status and liver function of young men before and after Ramadan fasting

Abstract: The objective of this study was to identify and analyse the hydration status and liver function of young men before and during Ramadan fasting (RF). The study design was a prospective cohort into 1 st period (one week before fasting) and 2 nd period (the last ten days of fasting). The subjects were 18 healthy young men (19-30 years old). Data on dietary intake were collected using food record 3x24h, body composition were collected using bioelectrical impedance analyser (BIA), hydration status, and liver functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Given that water intake is highly restricted within the period of Ramadan, in the first phase of this review, we will focus on the impact of fluid restriction on the levels of dehydration. Studies indicate that Ramadan fasting results in lower water intake during the month [ 10 , 11 ]. This potentially causes an alteration in kidney function, whereby water is reabsorbed by the body instead of being excreted in order to maintain fluid balance [ 11 ].…”
Section: Changes In Dietary Intakementioning
confidence: 99%
See 3 more Smart Citations
“…Given that water intake is highly restricted within the period of Ramadan, in the first phase of this review, we will focus on the impact of fluid restriction on the levels of dehydration. Studies indicate that Ramadan fasting results in lower water intake during the month [ 10 , 11 ]. This potentially causes an alteration in kidney function, whereby water is reabsorbed by the body instead of being excreted in order to maintain fluid balance [ 11 ].…”
Section: Changes In Dietary Intakementioning
confidence: 99%
“…Studies indicate that Ramadan fasting results in lower water intake during the month [ 10 , 11 ]. This potentially causes an alteration in kidney function, whereby water is reabsorbed by the body instead of being excreted in order to maintain fluid balance [ 11 ]. As such, there is effective water conservation during Ramadan fasting, by maximising urinary concentration as well as decreasing obligatory urine output [ 1 , 12 ].…”
Section: Changes In Dietary Intakementioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the mothers in NG (normal) were in the sufficient category. Hypo-hydration amongst Indonesian young men and women (18-30 years) is not uncommon, despite the homeostatic response to changes in osmolality which then activate the osmoreceptor to increase ADH level to stimulate thirst (Ibrahim et al 2018), a study found the majority of them were in the deficient category (81.9%) (Febriyani et al 2012).…”
Section: Macro and Micronutrient Intakementioning
confidence: 99%